Analisis Pengaruh Asset Growth, Debt to Total Assets Ratio, dan Return On Assets Terhadap Dividend Payout Ratio pada Perusahaan Go Public yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2011-2014 - B31112050, PURWANTO (Jurnal Manajemen Update, 2016)
The main purpose of people investing in companies that go public is to get dividend. Dividend is a part of the profit is given by the company to the shareholders who invest into companies. The amount of dividends distributed to shareholders depends on the dividend policy established by each company. The objective  aim  of  this  research  is  to  analyze  the  influence  of Return On Assets, Debt to Total Assets, and Asset Growth against Dividend Payout Ratio.   The population in this study is a company listed on the Bursa Efek Indonesia (BEI) in the period 2011-2014, there are 24 companies. Every company used as a sample is a company that has data Return On Assets, Debt to Total Asset, dan Assets Growth as well as pay a dividend in a row in the period 2011-2014. The sample is drawn using purposive sampling technique analyzed by using the two tail linear regression methodology. The results showing that the Return On Assets variable had positive significant influence to Dividend Payout Ratio, while Debt to Total Assets and Assets Growth had negative significant influence to Devidend Payout Ratio. The result of the analysis coefficient of determination (R²) is 44.10% with variable Dividend Payout Ratio can be explained by the variation of the variable Assets Growth, Debt to Total Assets, dan Return On Assets variable, while 55.90% is explained by other variables that not included in this research.   Keyword : Dividend Payout Ratio, Return On Assets, Debt to Total Assets, Asset Growth